Fungi prevalence in Lepidium peruvianum «Maca» flour come from markets of Andahuaylas, Ica and Cañete - Peru - Orellana, Alfonso (2005)
The fungi prevalence was determined in Lepidiumperuvianum «maca» flour, from a total of 60 samples collected in Andahuaylas (20), Ica (20) and Cañete (20) markets. Samples were proceed by the method of dilutions successive and culture in surface in Agar Potato Dextrose (APD). We found that 96,7% of the samples were contaminated; nine genera and 14 species of filamentous fungi were determinated, including a fungi classified as Mycelia sterilia. The colonies numbers goes from 33x104 to 61x10G UFC/g., and do not showed significant differences between markets. Penicillium and Fusarium were the genera with more incidence. The prevalence of high fungi contamination in maca flour suggests to continued studies to assess the effect and sanitary risk to human health.